Luta por direitos trabalhistas e luta pela terra no brejo paraibano : o caso da usina Santa Maria - Bernardo, Vilma Pires (2024)
This dissertation aims to understand the meanings of the fight for labor rights and the fight for land in the sugarcane agroindustry of brejo da Paraíba in the 1980s and 1990s, based on the case of the Santa Maria plant. The Santa Maria plant was installed in 1931 in the city of Areia-PB, a sugar and alcohol plant that had its bankruptcy declared in 1992, what was followed by mobilizations of rural workers for the payment of labor rights and, later, for the expropriation of the plant's land for the purposes of agrarian reform, which resulted in the creation of 10 rural settlements on land expropriated from the plant. But before the bankruptcy, the sugarcane workers in this agroindustry had already mobilized and organized. To realize the purpose of this research, documental research was carried out, using newspaper reports, labor lawsuits, the plant's bankruptcy process and others documents acessed through the interlocutors as sources, and field research, in which interviews were carried out with different social agents involved in these political fights, such as rural unionists, labor lawyers, nuns, activist and former rural workers of the plant. We understand that the fight for rights marked the rupture of the relation of personalized dependence with the plant owner. With the plant's bankruptcy, the fight for labor rights also made it possible to face the situation of material urgency that these workers, without payments and without work, experienced. Finally, we discuss that the decline of the sugarcane agroindustry in brejo da Paraíba opened the social horizons for multiple transformations in the region, that was object of intense political dispute in which the fight for land took on a material and symbolic meaning of reversing the process of expropriation of the residentes of the plant and made the peasant reconversion possible.